Numerical and Experimental Analysis of Roller Hemming on Door Panel’s Curved and Straight-Edge of Flat Plane - Chaohai Liu; Weimin Lin (Applied Sciences)
Owing to its enhanced production efficiency, roller hemming has become the mainstream process for forming and joining metal sheets in the automotive industry. This study investigates the roller hemming process of a specific car door panel through a combination of experimental analysis and finite element analysis (FEA) on both straight-edge and curved-edge flat surfaces. Consequently, the mechanical properties of the door panel, including tensile strength, yield strength, modulus of elasticity, and Poisson’s ratio, were estimated through tensile testing and then underwent finite element modeling. The simulation results demonstrated the varying distribution of stress during the rolling hemming process, with the highest stress concentration observed in the bending area. Additionally, creepage and growing results were acquired from both simulation and experimental data to validate the precision of the numerical model. A comparison was made between the experimental and simulation results of the external forces exerted by the roller on the panel. In both straight- and curved-edge sections, the external force during final hemming exceeded that during pre-hemming, as revealed by experimental measurements of both normal and tangential external forces, surpassing their corresponding simulated values.